Android-Based Learning Media Development Strategies During Pandemic Times To Improve Student Science Literature - Kevin William Andri Siahaan; Hisar Marulitua Manurung; Mungkap Mangapul Siahaan (Ilmu Inovasi Nusantara, 2021)
This study aims to develop appropriate android-based learning media to improve students' scientific literacy. This study uses the Four D model procedure. In addition to developing android-based media, this research also develops a syllabus, lesson plans, and scientific literacy instruments. This research was conducted in one of the Surya Private Junior High Schools in Pematangsiantar City. The validation of android-based learning media was carried out by three validators of media experts and material experts. Expert validation data analysis was carried out using the Pearson validation formula. The feasibility study of android-based learning products shows validity of 85% with very valid criteria. The results of the media feasibility study obtained an average score of 90%. The syllabus obtained an average score of 84%, lesson plans obtained an average score of 84%, and scientific literacy instruments obtained an average score of 85%. In conclusion, android-based media products on natural science material are feasible to be implemented in learning, especially during the covid-19 pandemic.